Soil phosphorus drives plant trait variations in a mature subtropical forest. (9th March 2022) - Cui, Erqian; Lu, Ruiling; Xu, Xiaoni; Sun, Huanfa; Qiao, Yang; Ping, Jiaye; Qiu, Shuying; Lin, Yihua; Bao, Jiehuan; Yong, Yutong; Zheng, Zemei; Yan, Enrong; et al.
Abstract: Earth system models are implementing soil phosphorus dynamic and plant functional traits to predict functional changes in global forests. However, the linkage between soil phosphorus and plant traits lacks empirical evidence, especially in mature forests. Here, we examined the soil phosphorus constraint on plant functional traits in a mature subtropical forest based on observations of 9943 individuals from 90 species in a 5‐ha forest dynamic plot and 405 individuals from 15 species in an adjacent 10‐year nutrient‐addition experiment. We first confirmed a pervasive phosphorus limitation on subtropical tree growth based on leaf N:P ratios. Then, we found that soil phosphorus dominated multidimensional trait variations in the 5‐ha forest dynamic plot. Soil phosphorus content explained 44% and 53% of the variance in the traits defining the main functional space across species and communities, respectively. Lastly, we found much stronger phosphorus effects on most plant functional traits than nitrogen at both species and community levels in the 10‐year nutrient‐addition experiment. This study provides evidence for the consistent pattern of soil phosphorus constraint on plant trait variations between the species and community levels in a mature evergreen broadleaf forest in the East Asian monsoon region. These findings shed light on the predominant role of soil phosphorus on plant functional trait variations in mature subtropical forests, providing new insights for models to incorporate soil phosphorus constraint in predicting future vegetation dynamics. Abstract : We applied multiple approaches in a mature tropical forest to test the linkage between soil phosphorus and plant traits. We confirmed a pervasive phosphorus limitation on subtropical tree growth based on leaf N:P ratios from 93 subtropical species. Analyses from the 5‐ha forest dynamic plot suggested that soil phosphorus dominated multidimensional trait variations. We then found much stronger phosphorus effects on most functional traits than nitrogen in the nutrient‐addition experiment. These multiple lines of evidence together shed light on the predominant role of soil phosphorus on plant functional trait variations in mature subtropical forests.